The soul of America [compact disc, unabridged] : the battle for our better angels - Meacham, Jon (Penguin Random House, 2018)
Pulitzer Prize-winning author Jon Meacham helps us understand the present moment in American politics and life by looking back at critical times in our history when hope overcame division and fear.